THE EFFECTS OF MEDITATION MINDFULNESS ON CONCENTRATION IN ARCHERY ATHLETES AT THE UNIMED ARCHERY CLUB - Thasya Selivya Valentine; Simatupang, Nurhayati; Kasih, Indra; Ockta, Yovhandra (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Archery athletes train their physique and technique in order to perform a series of bow and arrow pulls to the maximum, but athletes who can perform movements well during training may not necessarily be able to do it perfectly during the match. Athletes' concentration can be disrupted by various things when competing and affect the performance and achievements of athletes. The ability to concentrate is something that can be trained through mental training. This study aims to test whether there is an effect of Mindfulness Meditation, as one of the mental training methods, on the concentration of archery athletes. This study uses an experimental method with a pretest-posttest control group design. The subject of this study is 30 athletes from the Unimed Archery Club who are divided into experimental and control groups. The instrument used to measure the concentration of athletes is the Grid Concentration Exercise. Data were obtained by conducting pretest and posttest on both groups. Mindfulness Meditation treatment was given only to the experimental group. The results of the Wilcoxon Test analysis showed that there was a difference in concentration scores between after and before treatment in the experimental group (Sig.=0.027, p<0.05), meaning that the hypothesis "there is an effect of Mindfulness Meditation on concentration in Unimed Archery Club Archery Athletes" was accepted. The experimental group had a higher average gain score than the control group (5.5>0.76), which showed that Meditation Mindfulness had an effect on increasing the concentration of Archery athletes.